THE EFFECT OF PROMOTION AND TRANSFER ON JOB PERFORMANCE MEDIATED BY JOB SATISFACTION - Nurazisah Syahrir; Salju; Goso; Rahmawati (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2024)
This research is motivated by the importance of improving employee work performance at the East Luwu Regency Personnel and Human Resources Development Agency (BKPSDM) through effective human resource development. The phenomenon observed is that even though various promotions and transfers have been carried out, there are still gaps in employee work performance. This research uses a quantitative approach with a survey method involving 105 BKPSDM East Luwu Regency employees. Sampling used a saturated sample where all employees were sampled. Data was collected through questionnaires and data analysis was carried out using validity and reliability tests, descriptive tests and verification tests with the help of SmartPLS. The research results show that job promotions have a positive and significant effect on job satisfaction, but are not significant on direct work performance. Mutations have a positive and significant effect on job satisfaction, but are not significant on direct work performance. Job satisfaction has a positive and significant effect on work performance. Job promotions and transfers have a positive and significant effect on work performance through job satisfaction. Job promotions and transfers that are carried out well increase employee job satisfaction, which in turn increases their work performance.